Planlı dönemde Türkiye'de gemi inşa sanayii - Kaynak, Meltem (My University, 2019)
Dünya ticareti büyüdükçe uluslararası taşımacılıkta deniz yolunun önemi büyümektedir. Bu bağlamda deniz yolu taşımacılığı da daha fazla tercih edilmektedir. Deniz yolu taşımacılığın gelişmesine paralel gemi inşa sanayi de gelişme göstermektedir. Bu çalışmada Türkiye’de planlı dönemde (1960-1980) gemi inşa sanayinin durumu incelenmiştir. Ağırlıklı olarak kalkınma planları ve ilgili dönemde yürürlüğe giren mevzuattan yararlanılmıştır. Bu çalışmadan elde edilen sonuca göre; diğer dünya ülkelerinin oldukça gerisinde başlayan Türkiye’de gemi inşa sanayi, kalkınma planlarıyla devlet tarafından desteklenerek ilerleme kaydetmiştir. Önceleri ithalatla karşılanan talepler bu sektöre önem verilmesi ile bugün yurt içinde karşılanmaya başlanmıştır. Her ne kadar 2008 yılında güçlü bir kriz yaşanmış olsa da mevcut tersaneler ihraca yönelik de üretim yapılmaktadır.

As the world trade grows, the importance of maritime transport in international transport grows too. And because of this, maritime transport is more preferred. According to this development of maritime transport, shipbuilding industry also grows. In this study, shipbuilding industry was examined ın the planned period in Turkey (1960-1980). Mostly development plans and the legislation that came into force in the relevant period is utilized. According to the results of this study, shipbuilding in Turkey which started late compared to other countries, has made progress by development plans supported by the state. The demands that used to be compensated by the imports before, with the importance given to this sector, it has started to be compensated in Turkey today. Although there was a strong crisis in 2008, the existing shipyards produce for export.As the world trade grows, the importance of maritime transport in international transport grows too. And because of this, maritime transport is more preferred. According to this development of maritime transport, shipbuilding industry also grows. In this study, shipbuilding industry was examined ın the planned period in Turkey (1960-1980). Mostly development plans and the legislation that came into force in the relevant period is utilized. According to the results of this study, starting behind other countries in the world shipbuilding industry in Turkey, supported by the state through development plans. The demands that used to be compensated by the imports before, with the importance given to this sector, it has started to be compensated in Turkey today. Although there was a strong crisis in 2008, the existing shipyards produce for export.
Keywords: Gemi İnşa Sanayii; Planlı Dönem; Planned Perıud; Turkish Economy; Türkiye Ekonomisi Shipbuilding Industry